2017
DOI: 10.1111/aor.13065
|View full text |Cite
|
Sign up to set email alerts
|

Native Bovine and Porcine Pericardia Respond to Load With Additive Recruitment of Collagen Fibers

Abstract: Bovine and porcine pericardia are currently used for manufacturing prosthetic heart valves: their design has become an increasingly important area of investigation in parallel with progressively expanding indications for the transcutaneous approach to heart valves replacement. Before being cut and shaped, pericardial tissues are expected to be properly characterized. Actually, the mechanical assessment of these biomaterials lacks standardized protocols. In particular, the role of preconditioning for achieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A comparative assessment of acellular pericardia from different species is still incomplete, as opposed to the most largely implanted GA-preserved native tissues [34,35]. Such information is of paramount importance in developing effective therapeutic strategies targeted for each surgical indication.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative assessment of acellular pericardia from different species is still incomplete, as opposed to the most largely implanted GA-preserved native tissues [34,35]. Such information is of paramount importance in developing effective therapeutic strategies targeted for each surgical indication.…”
Section: Introductionmentioning
confidence: 99%
“…Sulejmani et al found that the smooth side of APP contributed more to its mechanical properties, and especially to its anisotropic material response (Sulejmani, Caballero, Martin, Pham, & Sun, 2019). Interestingly, Bagno et al suggested that the collagen fiber bundles aligned in different directions in APP became more oriented with increasing applied stresses (Bagno et al, 2018). Thus, the special components, distinct microstructure, and pattern of mechanical response contributed to the better mechanical properties of APP.…”
Section: Discussionmentioning
confidence: 99%
“…Andrea Bagno et al of the University of Padova, Padova, Italy, investigated the mechanical response to uniaxial load of native bovine and porcine pericardia, with and without preconditioning and the mechanical behavior of pericardia. They demonstrated that: (i) pericardial tissue samples hold memory of the loading history but just within the extent of the deformation applied; (ii) the behavior of native bovine and porcine pericardia in response to load is explained by a mechanism based on the additive recruitment of collagen fibers; (iii) the current concept that plasticity is absent in pericardium has to be at least in part reconsidered.…”
Section: Tissue Engineeringmentioning
confidence: 99%